Penerapan Pendekatan Kontekstual Dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris Pada Siswa Kelas VIII A Smp Negeri 16 Bulukumba - Parah, Nurul (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This research aims to investigate the effectiveness of implementing a contextual approach to improve vocabulary mastery of eighth-grade students. A classroom action research was conducted over two cycles in a secondary school. The research participants consisted of 30 eighth-grade students who had limitations in vocabulary mastery. This study utilized a qualitative approach with a classroom action research method. Data were collected through classroom observations, documentation, and written tests. In each cycle, intervention actions were conducted based on the principles of the contextual approach. The interventions involved using real-world contexts and problem-based activities to introduce and consolidate new vocabulary. The results of the research indicated that the implementation of the contextual approach significantly improved the vocabulary mastery of the eighth-grade students. At the beginning of the study, only 30% of the students achieved an adequate level of vocabulary mastery. However, after two cycles of research, the percentage of students reaching that level increased to 90%. Additionally, an improvement in vocabulary mastery was also evident from the results of the written tests, which showed an increase in the students' average scores from 63 to 84. Furthermore, this research also demonstrated that the contextual approach provided additional advantages, such as enhancing student motivation and engagement in learning. Students showed greater interest in learning vocabulary when real-world contexts were used, and they were more active in applying new vocabulary in everyday situations. Keywords: Learning outcome, Contextual Approach, Use of Vocabulary